Chronic kidney disease in patients with acute myocardial infarction without ST segment elevation: therapeutic nihilism? - Santos,M. Teresa (2014)
Background: Chronic kidney disease is an independent risk factor for mortality after acute coronary syndrome. Our aim was to characterize the in-hospital management and outcomes of patients with chronic kidney disease in the setting of non-ST-segment elevation myocardial infarction. Methods: This is a single centre, prospective and observational study, including 230 consecutive patients admitted with the diagnosis of non-ST-segment elevation myocardial infarction. Glomerular filtration rate was estimated using the Modification of Diet in Renal Disease Study formula and in-hospital therapies and outcomes were recorded. Results: Overall, 25.7% of patients had moderate to severe chronic kidney disease. Patients with chronic kidney disease were less likely to undergo coronary angiography (27% vs. 81%, p < 0.001) and receive less evidence-based therapies, including aspirin (86.4% vs. 98.8%, p < 0.001), clopidogrel (74.6% vs. 90.6%, p = 0.002), angiotensin-converting enzyme inhibitor and/or angiotensin II receptor blocker (54.2% vs. 90.6%, p < 0.001) or anticoagulant therapy (83.1% vs. 95.9%, p = 0.001). In addition, the in-hospital mortality was higher for patients with chronic kidney disease (15.3% vs. 2.9%; p = 0.002). Conclusion: Non-ST-segment elevation myocardial infarction patients with chronic kidney disease have higher in-hospital mortality. The underuse of evidence-based therapies and interventions can help to explain these results.